Oxidative stress in the pathogenesis of Fuchs endothelial corneal dystrophy - Wójcik, Katarzyna A.; Błasiak, Janusz; Kamińska, Anna; Kurowska, Anna; Szaflik, Jerzy; Szaflik, Jacek P. (Klinika Oczna / Acta Ophthalmologica Polonica, 2013)
Fuchs endothelial corneal dystrophy is a disease which occurs after the fourth decade of life. This disorder is characterized by the formation of excrescences growing from the Descemet membrane, called cormea guttata, and changes in the corneal endothelial cell density and morphology. The pathogenesis of Fuchs endothelial corneal dystrophy is not completely known. Autosomal dominant mode of inheritance observed in some cases of Fuchs endothelial corneal dystrophy suggests possible genetic etiology of the disease. Environmental factors also seem to be associated with Fuchs endothelial corneal dystrophy. A growing number of reports suggest an important role of oxidative stress in this disorder. An increased level of toxic products of reactive oxygen species activity and the decreased expression of antioxidant enzymes, including thioredoxin reductase, metallothionein 3 and superoxide dismutase 2, were detected in corneas of patients with Fuchs endothelial corneal dystrophy. The imbalance between the production and neutralization of reactive oxygen species may result in oxidative stress exerting a harmful effect on cellular components, leading to molecular and cellular damage. Mitochondria may be a key target of alterations seen in Fuchs endothelial corneal dystrophy. An increased level of oxidative mitochondrial DNA (mtDNA) damage was detected in corneas of patients with Fuchs endothelial corneal dystrophy. Disturbance in mtDNA may cause loss of integrity of inner mitochondrial membrane potential and activate the inner apoptotic pathway. Consequently, oxidative stress may contribute to the changes in endothelial morphology and apoptosis observed in Fuchs endothelial corneal dystrophy.